The Development of Worksheet Based on Guided Discovery Learning Method Helped by PhET Simulations Interactive Media in Newton's Laws of Motion to Improve Learning Outcomes and Interest of Vocational Education 10th Grade Students - Nurahman, Arip; Widodo, Widodo; Ishafit, Ishafit; Saulon, Butch O. (Universitas Ahmad Dahlan, 2018)
This research was aimed to produce students worksheet (LKPD) based on PhET Interactive Simulations Software in cognitive through the application of physics-based guided discovery learning model that is devoted to the concept of Newton's Law of Motion. Guided Discovery-based approach is expected and is believed to develop students' skills in various aspects of one study that showed achievement levels mastery of physics students after participating in the learning process under the expected educational purposes. Researchers conducted a study on the process of learning physics for the discovery-oriented at vocational senior high school students in Newton's law of motion with R&D. Subjects were students of class X TKRO in the first semester of the academic year 2018-2019 in vocational high school in Ciamis, West Java Province as many as 35 students. Data collected through tests, observations and interviews.Â